Evaluation of rice cultivars for resistance to Diopsis longicornis (Diptera: Diopsidae) - Alam, M.S. (1988)
Screen house evaluation of 3,002 rice accessions (2,951 Oriya saliva L. and 51 O. glaberrima Strudel) from 47 countries led to the identification of 18 accessions with resistant or moderately resistant reactions to Diopsies longicornis Macquart. The resistant accessions came from four countries. Fourteen (78%) of the selected accessions were found among the O. glaberrima. All of the resistant and moderately resistant accessions are from regions where D. longicornis is an important pest except for one accession from India, which is outside the normal range of D. longicornis distribution.